Analysis of Carbon Corrosion in Anode under Fuel Starvation Using On-Line Mass Spectrometry in Polymer Electrolyte Membrane Fuel Cells. Issue 14 (1st January 2017) - Lim, Katie Heeyum; Lee, Woong Hee; Jeong, Yoonjae; Kim, Hansung
Abstract : The precise mechanism of performance degradation in polymer electrolyte membrane fuel cells (PEMFCs) under the fuel starvation condition is investigated by simultaneously monitoring the potential behavior and exhaust gas from the anode using the hydrogen reference electrode and in situ online mass spectrometry. Interestingly, the water electrolysis begins at a lower potential range, and carbon oxidation occurs at a higher range as the alternative reaction to hydrogen oxidation. Thus, carbon corrosion, which is detrimental to cell performance, can be reduced by extending the duration of the water electrolysis reaction. In this regard, the introductions of the graphitized carbon support and water electrolysis catalyst to anode are effective in alleviating the damage due to fuel starvation by rendering the dominant alternative reaction to continue the water electrolysis.